The Influence of Community’s Instagram Exposure and Content Towards Mothers’ Attitude on Mental Health - Ruvira Arindita; Muchammad Nasucha (Ultimacomm: Jurnal Ilmu Komunikasi, 2023)
The vast improvement of technology opened opportunity for everyone to build community, including mothers. Transition to motherhood is challenging for women’s mental health. Halo Ibu Community is providing media and space for mothers to support each other via @haloibuid. This study aims to find out whether there is influence of exposure and content of Instagram @haloibuid towards the attitude of mothers regarding mental health. The concepts used on this research are namely stimulus response theory, social media exposure, Instagram content, attitude, and mental health. The population of this research is followers of @haloibuid. This research is conducted by distributing the questionnaire to 100 mothers who are followers of @haloibu.id and the active member of community. The result noted that coefficient determinant (R2) is 45,8%. This indicates that exposure and content simultaneously contribute to the attitude of mothers on mental health for 45,8%. The coefficient test (T-test) result noted that exposure and content have partially significant influence towards attitude for respectively 35.5% and 37.4%. Direction and value prediction are shown by this multiple regression analysis Y= 6.724 + 0.389 X1 + 0.468 X2. This implies that if the exposure of Instagram is increasing 1 score, then the attitude of mothers is increasing for 0.389 score and if the content Instagram is increasing 1 score, then the attitude of mothers is increasing for 0.468 score. These results illustrate that exposure and content of Instagram @haloibu.id have positive and significant influence over the followers’ attitude regarding mental health.